THE IMPACT OF ARDUINO CODING LEARNING ON COMPUTATIONAL THINKING SKILLS OF JUNIOR HIGH SCHOOL STUDENTS - Rahmat Setiawan; Sahiruddin Sahiruddin; Firman Firman; Endra Putra Raharja (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
This study aimed to examine the effect of Arduino-based coding learning on junior high school students' computational thinking skills. A quasi-experimental method with a pretest-posttest control group design was employed. Twenty junior high school students participated in the study and were divided into two groups: 10 students in the experimental group received Arduino-based coding instruction, while 10 students in the control group received conventional coding instruction. Data were collected using a computational thinking skills test administered before and after the intervention. The data were analyzed using descriptive statistics, normality and homogeneity tests, paired-samples t-tests, and an independent-samples t-test. The results showed that the experimental group's mean score increased from 58.40 to 84.60, whereas the control group's mean score increased from 57.90 to 68.30. The independent-samples t-test revealed a significant difference between the two groups (t = 6.02, p < 0.001). Furthermore, students in the experimental group achieved higher scores across all computational thinking dimensions, including decomposition, pattern recognition, abstraction, and algorithmic thinking. These findings indicate that Arduino-based coding learning is more effective than conventional coding instruction in improving junior high school students' computational thinking skills.